(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India is without doubt a growth economy and many considerit an attractive country to invest in, particularly its rapidly growing andchanging retail market. However, Foreign Direct Investment (FDI) is restrictedin the retail sector, and despite many years of debate, the regulations arestill only changing very slowly and there are still lots of uncertainties.Foreign investors are watching India, ready for a piece of the action in theretail market, but there are still plenty of uncertainties, restrictions andpotential socio- economic risks. India should be well on the radar for foreign retailerswas recently supported by A.T. Kearney, whose 2011 global retail developmentindex ranks the nation as fourth globally. India’s retail industry is estimatedto be worth approximately US 411.28 billion and is still growing, expected toreach US 804.06 billion in 2015. As part of the economic liberalizationprocess set in place by the industrial policy of 1991, the Indian governmenthas open the retail sector to FDI slowly through a series of step. Objectives of this paper are to investigate the Indianmarket place and review current policy and regulations with a view point offoreign investors so as to gain an understanding of the current position onFDI, as well as an overview of the Indian policy and regulatory environment.